Causal Effect of Serum Magnesium on Osteoporosis and Cardiometabolic Diseases - He, Bin; Xia, Liang; Zhao, Jinqiu; Yin, Lifeng; Zhang, Muzi; Quan, Zhengxue; Ou, Yunsheng; Huang, Wei (Frontiers in Nutrition, 2021)
Serum magnesium is associated with osteoporosis and cardiometabolic diseases, but their causal associations remains elusive. We used the two-sample Mendelian randomization (MR) study to explore the causal roles of serum magnesium on osteoporosis and cardiometabolic diseases by using the aggregated genome-wide association studies (GWASs). Six single-nucleotide polymorphisms (SNPs, P<5×10−8) associated with serum magnesium concentrations were all used as instrumental variables. A genetic predisposition to higher serum magnesium concentrations was inversely associated with lower lumbar spine bone mineral density (BMD, beta-estimate: -1.982, 95% CI: -3.328 to -0.635, SE:0.687, P-value=0.004), which was further confirmed by multiple sensitivity analyses. There was limited evidence of associations between serum magnesium and type 2 diabetes, coronary artery disease, heart failure and atrial fibrillation. This study provides strong evidence that genetically increased serum magnesium concentrations was causally associated with low lumbar spine BMD, and suggested that serum magnesium concentrations may be crucial to prevent osteoporosis.